External Validation of the NECPAL CCOMS-ICO Prognostic Tool for Early Palliative Care and Mortality Prediction in Patients with Advanced Chronic Conditions: A Prospective Observational Study Protocol - Ana Bustamante-Fermosel; Elena Díaz-Sánchez; Natalia Pavón-Muñoz; Laetitia Hennekinne; Fuensanta Gil-Gil; Helena Notario-Leo; Alicia Sánchez-Pizarro; Marta Bustamante-Vega; Juan Torres-Macho; Anabel Franco-Moreno; on behalf of the COMPASS Research Group (Methods and Protocols, 2025)
Early initiation of palliative care in patients with advanced chronic conditions significantly improves their quality of care; however, variability in disease trajectories complicates such interventions’ timing. The NECPAL CCOMS-ICO prognostic tool was developed as a straightforward instrument to help healthcare providers in all clinical settings promptly identify patients with advanced chronic conditions who require palliative care, thereby enhancing service planning and delivery. Its latest version, 4.0, 2021, for the first time, incorporates a patient survival estimation. Nevertheless, validation is necessary. This study aims to validate the NECPAL version 4.0 tool in an independent cohort. It is an observational, prospective study involving outpatients and hospitalized non-randomized patients at Hospital Universitario Infanta Leonor–Virgen de la Torre in Madrid, Spain, all of whom have at least one advanced chronic condition. The study is scheduled to last 6 years, including a recruitment period of 30 months starting 1 February 2024, followed by a 12-month follow-up period for each patient. This is the first prospective study designed to validate the NECPAL version 4.0 instrument. Implementing this tool would allow the identification of patients with advanced chronic conditions and unmet palliative care needs and determine the more appropriate care pathway at the proper moment.